Parasitism of The Rice Brown Planthopper Eggs in Various Periods of Time of The Day - Siti Haryati; Y. Andi Trisyono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2016)
The rice brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae) is an important pest of rice. Since at the early stage, this pest is infested by parasitoids, but most cultural practices do not consider the existences of parasitoids in rice ecosystem. This study was aimed to determine the level of parasitism on N. lugens with regard to the time of the day. This information would be useful to minimize the effect of insecticide application to the parasitoids. Trapping of egg parasitoids in rice ecosystem was conducted every two hours from 05.00 a.m. until 04.00 p.m. Parasitism occured as early as at 05.00 a.m. (12.26% of the total parasitoid found), reached the peak abundance at 11.00 a.m. (36.13%), and decreased at 01.00 p.m. The parasitism level varied from 1.12 to 8.51% at 66 days after planting. The highest number of parasitoids and the highest parasitism level occured when trapping was conducted between 11.00 a.m.−01.00 p.m.. Before and after this period of time, the number of parasitoid emerged and parasitism were low. This suggest that if insecticide is necessary, it should be applied in the early morning or late afternoon. INTISARIWereng batang padi cokelat, Nilaparvata lugens (Hemiptera: Delphacidae), merupakan salah satu hama penting padi. Praktik budidaya pertanian padi belum memperhatikan aktivitas parasitoid dalam ekosistem. Tujuan dari penelitian ini yaitu untuk mengetahui tingkat parasitasi telur N. lugens pada beberapa waktu dalam sehari. Informasi ini akan bermanfaat untuk mengurangi dampak aplikasi insektisida terhadap parasitoid. Pemerangkapan parasitoid telur N. lugens di lahan padi dilakukan setiap dua jam yang dimulai pada pukul 05.00 sampai pukul 16.00. Parasitoid telur N. lugens mulai aktif pada pukul 05.00 (12,26%), mencapai puncaknya pukul 11.00 (36,13%), dan mulai mengalami penurunan pada pukul 13.00. Tingkat parasitasi pada tanaman padi umur 66 hari setelah tanam berkisar mulai 1,12−8,51%. Hasil pemerangkapan menunjukkan bahwa jumlah parasitoid yang paling banyak muncul dan tingkat parasitisme tinggi terjadi pada waktu pemerangkapan yang dilakukan pada pukul 11.00−13.00. Sebelum dan sesudah waktu pemerangkapan tersebut jumlah parasitoid dan tingkat parasitisme rendah. Hal ini menunjukkan bahwa apabila aplikasi insektisida diperlukan, maka harus dilakukan di pagi hari atau sore hari.